Th17 cells and innate immunity - Netea, Mihai (Henry Stewart Talks, 2012)
Resistance to infection, Involvement of innate and adaptive immune responses, Innate immunity modulates Th-responses, Th17 are crucial for mucosal host defense, Deficiencies in Th17 in patients lead to mucosal fungal and bacterial infections